2019
DOI: 10.3390/jcm8050630
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Health and Oral Microbiota in Patients with Rheumatoid Arthritis

Abstract: This study aimed to investigate the periodontal health of patients with established rheumatoid arthritis (RA) in relation to oral microbiota, systemic and oral inflammatory mediators, and RA disease activity. Forty patients underwent full-mouth dental/periodontal and rheumatological examination, including collection of blood, saliva, gingival crevicular fluid (GCF) and subgingival plaque. Composition of plaque and saliva microbiota were analysed using 16S rRNA sequencing and levels of inflammatory mediators by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 76 publications
5
80
0
Order By: Relevance
“…To determine potential causality between periodontitis and RA, presence and production of RA‐associated antibodies in the periodontium should be investigated, preferably with assessment of the microbial composition of the dental biofilm. In this respect, Eriksson et al, () very recently showed that most RA patients with moderate or severe periodontitis were seropositive for ACPA (86%) as well as that these patients had a subgingival microbial profile that differed from RA patients with no or mild periodontitis and had higher levels of oral and systemic inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…To determine potential causality between periodontitis and RA, presence and production of RA‐associated antibodies in the periodontium should be investigated, preferably with assessment of the microbial composition of the dental biofilm. In this respect, Eriksson et al, () very recently showed that most RA patients with moderate or severe periodontitis were seropositive for ACPA (86%) as well as that these patients had a subgingival microbial profile that differed from RA patients with no or mild periodontitis and had higher levels of oral and systemic inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches have been used to address a potential association between P. gingivalis and RA, many of which have shown inconsistent or inconclusive results. These include: (1) bacterial detection in gingival tissue, subgingival plaque and/or gingival crevicular fluid (GCF) either by staining using anti- P. gingivalis antibodies, bacterial culture, and/or DNA amplification (PCR) [101,102,103,104,105,106,107]; (2) metagenomic sequencing in saliva and subgingival plaque, which surveys complex microbial communities [103,106,108,109,110,111,112]; and (3) measuring antibodies to P. gingivalis in serum [101,113,114,115,116,117,118,119,120,121,122,123,124,125], which in contrast to the other assays that detect the existing bacteria in the mouth, it is an indirect test that determines past or present exposure to P. gingivalis .…”
Section: P Gingivalis In Ra Pathogenesismentioning
confidence: 99%
“…Interestingly, associations between bacterial measures and prediabetes are consistently stronger than those between periodontitis and prediabetes. Furthermore, there is accumulating evidence on the role of P. gingivalis in rheumatoid arthritis [37,38]. A prospective study on the association between pancreatic cancer and the oral microbiome revealed that the carriage of P. gingivalis and A. actinomycetemcomitans is a subsequent risk for this highly lethal cancer type [39].…”
Section: Pathogenic Biofilmsmentioning
confidence: 99%